The RET inhibitor pralsetinib suppresses TMZ-resistant glioma growth by regulating spermine production - Ma, Lingyun; Gong, Hang; Sun, Wei; Deng, Jialing; Zhang, Qinghua; Niu, Jianzhao; Sun, Huimin; Han, Xue; Du, Tingting; Xue, Nina; Ji, Ming; Liu, Qian (Frontiers in Pharmacology, 2025)
ObjectiveGlioma is the most common malignant tumor of the central nervous system and is characterized by altered cellular metabolism. Although temozolomide (TMZ)-based adjuvant treatment has improved overall patient survival, clinical outcomes remain unsatisfactory. TMZ resistance is a major contributing factor. The mechanisms underlying TMZ resistance are highly complex. This study aimed to elucidate the role of spermine in TMZ resistance and to assess the antitumor activity of kinase inhibitors against TMZ-resistant glioma.MethodsThe TCGA data from glioma patients treated with TMZ was analyzed and metabolomic analysis of both TMZ-sensitive and TMZ-resistant glioma cells was performed. A series of compounds in both TMZ-sensitive and TMZ-resistant glioma cells were screened, and their brain penetration capacity was tested by MacroFlux assay. The antitumor activity of pralsetinib was evaluated in vitro and in vivo.ResultsIn this study, we found that spermine synthase (SMS) was highly expressed in gliomas that showed a poor clinical response to TMZ treatment. Spermine, the metabolic product of SMS, was also elevated in TMZ-resistant glioma cells and promoted their proliferation. Further investigation revealed that pralsetinib, a selective RET inhibitor, exhibited significant antitumor activity against TMZ-resistant glioma cells both in vitro and in vivo. Mechanistically, pralsetinib inhibited the spermine-induced activation of the PI3K/AKT pathway and downregulated SMS expression, leading to reduced spermine production.ConclusionOur findings reveal the role of spermine in TMZ-resistant glioma and suggest a potential new pharmacological application for pralsetinib in the glioma treatment.